KAJIAN KONSEP OPERASIONAL PEMELIHARAAN GEDUNG SMA BINA GENERASI BANGSA MEULABOH ACEH BARAT - Mawardi, Edi; Aulia, Teuku Budi; Abdullah, Abdullah (JURNAL TEKNIK SIPIL, 2018)
Abstract: Building school as a public facility which is a means of education for the smooth process of teaching and learning. With the concept of operational maintenance of the building is less good because the various functions of building facilities declined and affect the quality and comfort of the building. If the damage to building components is left then slowly the service life of the building will decrease. Seeing the function of the building of the Senior High School (SMA) Bina Generasi Bangsa Meulaboh, it should have got the concept of good maintenance operations so that the reliability and feasibility of buildings in the architecture, structure, and utilities are maintained and functioning optimally. The objectives of the study were to find out the operational concept of building maintenance, to identify the percentage of damage, to estimate the maintenance cost and maintenance priority sequence. Analytical methods used statistical methods The result of the analysis is heavy damage happened to utility component equal to 84,04%, moderate damage at component of architecture equal to 50,24% and light damage to structural component equal to 1,56%. The calculation for maintenance cost of 13.08% of the price of the construction of the state building, in accordance with the Ministerial Decree No.24 / PRT / M / 2008 of the building entered the category of light maintenance.. The result of hammer test test shows that the compressive strength value of the structural component is low below that required by SNI 03-2847-2002 for the 225 kg / cm multi-storey building.Abstrak: Bangunan sekolah sebagai faslitas umum yang merupakan sarana pendidikan untuk kelancaran proses belajar mengajar. Dengan konsep operasional pemeliharaan gedung yang kurang baik menyebabkan berbagai fungsi fasilitas gedung semakin menurun dan mempengaruhi kualitas dan kenyamanan gedung. Apabila kerusakan komponen gedung dibiarkan maka secara perlahan umur layan gedung akan berkurang. Melihat fungsi dari bangunan Sekolah Menengah Atas (SMA) Bina Generasi Bangsa Meulaboh, maka sudah seharusnya bangunan ini mendapat konsep operasional pemeliharaan yang baik agar keandalan dan kelayakan bangunan secara arsitektur, struktur, maupun utilitas tetap terjaga dan berfungsi secara optimal. Tujuan penelitian untuk mengetahui konsep operasional pemeliharaan gedung, mengidentifikasikan persentase kerusakan, memperkirakan besarnya biaya pemeliharaan dan urutan prioritas pemeliharaan. Metode analisis yang digunakan metode statistik. Hasil analisis tersebut kerusakan berat terjadi pada komponen utilitas sebesar 84,04%, kerusakan sedang pada komponen asitektur sebesar 50,24% dan kerusakan ringan pada komponen struktural sebesar 1,56%. Perhitungan untuk biaya pemeliharaan sebesar 13,08% dari harga pembangunan gedung negara, sesuai dengan permen PU No.24/PRT/M/2008 gedung tersebut masuk katagori pemeliharaan ringan. Hasil pengujian hammer test menunjukan bahwa nilai kuat tekan pada komponen struktural tergolong rendah dibawah yang disyaratkan SNI 03-2847-2002 untuk bangunan bertingkat 225 kg/cm.